Kekuatan Keuangan di Balik Manajemen Laba: Studi Tentang Pertumbuhan Penjualan, Perencanaan Pajak, Ukuran Perusahaan, dan Profitabilitas - Anam, Saiful (Universitas Jember, 2024)
This study aims to examine of Sales Growth, Tax Planning, Company Size, and Profitability on Earnings Management, A Case Study of Consumer Goods Sector Companies Listed on the IDX The research encompasses all businesses within the consumer goods sector listed on the Indonesian Stock Exchange during that period. A purposive sampling method was employed, with a sample size of 45 companies. For firms in the food and beverage sector listed. The findings from firms in the food and beverage sector (2018–2021) show that sales growth and profitability have a partial yet significant impact on earnings management, suggesting that companies with higher sales growth or profitability may engage in such practices to maintain investor confidence or meet expectations. In contrast, tax planning and company size do not exhibit a partial effect, challenging the assumption that larger firms or those engaged in tax planning are more likely to manipulate earnings. This may reflect stricter regulations or increased transparency in this sector. Keywords: Sales Growth, Tax Planning, Company Size, Profitability and Profit Management